Descemet membrane endothelial keratoplasty with a stromal rim in the treatment of posterior polymorphous corneal dystrophy - Studeny, Pavel; Jirsova, Katerina; Kuchynka, Pavel; Liskova, Petra (Indian journal of ophthalmology, 2012)
A 20-year-old patient, diagnosed with posterior polymorphous corneal dystrophy, developed corneal edema for which he underwent Descemet membrane endothelial keratoplasty with a stromal rim (DMEK-S) in the right eye. No intra- or postoperative complications were noted. At the last follow-up 2 years and 9 months after the procedure, the best corrected visual acuity was 1.0 and endothelial cell density declined from 3533 cells/mm 2 to 1012 cells/mm 2 . Despite the endothelial cell loss, DMEK-S appears to be a good alternative to other surgical techniques for the treatment of corneal endotheliopathies, and it may be of benefit to young patients.
Keywords: Descemet Membrane; Male; Endothelium, Corneal; Time Factors; Corneal Stroma; časové faktory; Descemetova membrána; Humans; zadní lamelární keratoplastika; Descemet Stripping Endothelial Keratoplasty; zraková ostrost; mužské pohlaví; mladiství; stroma rohovky; následné studie; Follow-Up Studies; rohovkový endotel; Visual Acuity; Fuchs' Endothelial Dystrophy; Adolescent; Fuchsova endoteliální dystrofie; lidé